Maternal syphilis treatment and pregnancy outcomes: a retrospective study in Jiangxi Province, China - Zhihua Wan; Huan Zhang; Haigang Xu; Yang Hu; Cai Tan; Yuling Tao (BMC, 2020)
Abstract Background Studies investigating the associations of maternal syphilis treatment with birth outcomes mainly concentrated in economically developed areas. Limited data are available in economically underdeveloped areas, such as Jiangxi Province. The study aims to investigate the impact of maternal treatment on birth outcomes in Jiangxi Province, China. Methods Data were obtained from the China's Information System of Prevention of Mother-to-Child Transmission in Jiangxi Province. All syphilis infected pregnant women who delivered ≥28 gestational weeks and were registered in this system between 1 January 2013 and 31 December 2019 were enrolled. Pregnancy outcomes were evaluated by group-specific analyses according to their treatment status, adequacy and initiation time. Results 4210 syphilis infected pregnant women were included in the analyses. Infants born to untreated mothers (n = 1364) were at significantly higher risk for stillbirth (adjusted odds ratio (aOR) = 1.74, 95% CI, 1.01-3.00, P = 0.045), preterm birth (aOR = 1.27, 95% CI, 1.02-1.59, P = 0.034) and low birth weight (LBW) (aOR = 1.44; 95% CI, 1.11-1.86, P = 0.006) than those born to treated mothers (n = 2846) after adjustment for confounding factors. A significantly higher risk of stillbirth (aOR = 3.68; 95% CI, 1.62-8.34, P = 0.002), preterm birth (aOR = 2.26; 95% CI, 1.71-3.00, P < 0.001), LBW (aOR = 2.23; 95% CI, 1.59-3.14, P < 0.001) and congenital syphilis (CS) (aOR = 3.63; 95% CI, 1.80-7.31, P < 0.001) was found in infants exposed to mothers treated inadequately (n = 1299) than those treated adequately (n = 1547). No pregnant women who initiated the treatment in the first trimester (n = 682) delivered a neonatal CS case. Compared with mothers who initiated treatment in the first trimester (n = 682), those initiated in the third trimester (n = 1234) suffered an increased risk of stillbirth (aOR = 4.48; 95% CI, 1.31-15.30, P = 0.017), preterm birth (aOR = 2.34; 95% CI, 1.61-3.40, P < 0.001) and LBW (aOR = 3.25; 95% CI, 1.97-5.37, P < 0.001). Conclusions Maternal treatment, especially early and adequate treatment, plays a crucial role in mitigating adverse pregnancy outcomes among syphilis infected women.